Aorto-Enterie Fistula: A dilemma for the Endoscopist as a rare cause of gastro-intestinal bleeding - (:unkn) unknown (ARSMB-KVBMG, 2009)
A 78-year-old man with a history of aorta-femoral graft operation was admitted to the hospital with symptoms of syncope, melena and haematemesis. He reported several episodes of melena during the previous year for which he underwent repeated gastro-intestinal endoscopic examinations, which were unable to show the site of the gastro-intestinal bleeding. The third upper gastro-intestinal endoscopic examination disclosed a yellowish ulcerative lesion with irregular borders in the third part of the duodenum, which was considered to be a fistula, between the aorta and the duodenum. The patient underwent an explorative operation that revealed an intact aortic graft, firmly adherent to the duodenal wall, and the duodenum that was eroded in the third portion. The duodenum was transected and a duodenoduo- denostomy was performed. Although re-bleeding did not occur, the patient died of sepsis eight days after the operation. Aorto-enteric fistulae can be missed due to the common practice of limiting the endoscopic examination to the second part of the duodenum and not considering them in the differential diagnosis of gastro-intestinal bleeding because of their rarity. Possibly, a number of prior endoscopic examinations may be inconclusive until a correct diagnosis is reached in most of the cases.
Keywords: Aorto-enteric fistula; Upper gastro-intestinal bleeding